Effect of the use of remineralization agents before resin infiltration on the treatment of initial enamel lesions: an in-vitro study - Bengü Doğu Kaya; Aybike Manav Özen; Pınar Yılmaz Atalı; Ayça Sarıalioğlu Güngör; Evrim Dalkılıç; Elif Alkan; Dilek Tağtekin; Cafer Türkmen (BMC, 2024)
Abstract Aim This study aimed to evaluate the effect of the use of remineralization agents before the application of resin infiltration on the treatment of initial enamel lesions. Materials and methods Eighty buccal enamel samples were prepared from human molars, and artificial initial lesions were formed after 96 h of incubation with a demineralizing solution. The samples were randomly divided into 8 groups (n = 10) including a remineralizing agent (Tooth Mousse, Medical Mineral Gel, Remin Pro), resin infiltration (ICON), and a combined treatment of both. Remineralizing agents were applied in pH cycle for 7 days. Baseline, demineralization, and after-treatment fluorescence (FluoreCam and DIAGNOdent Pen), surface microhardness (HMV-2T), surface roughness (M300C), OCT (Maestro-2) and ultrasonic system (Novascope 4500) data were obtained for all groups. The sample surfaces were examined under SEM/EDX (SU3500) at x1000. Data were statistically analyzed using the Two-Way Robust ANOVA and Bonferroni tests (p < 0.05). Results There was no statistically significant difference between the groups for microhardness, roughness, OCT, DIAGNOdent Pen, ultrasound, and FluoreCam size/intensity values (p = 0.582; p = 0.963; p = 0.884; p = 0.923; p = 0.051; p = 0.268; p = 0.793 respectively). The effect of the treatment procedure showed a significant difference (p < 0.001), except for the roughness values (p = 0.984). The lowest Calcium (Ca) ratio (%atomic) was observed in the RI group in the EDX analysis. Conclusion Remineralizing agents and resin infiltration methods may be used in combination or alone in the treatment of initial enamel lesions. Combining remineralizing agents with resin infiltration does not alter the efficacy of the treatment.